Understanding COVID-19 through the Dental Lens - Sarah Ghafoor; Ansa Javed Akram (BioMedica, 2020)
Corona virus Disease-19 (COVID-19) is a global health pandemic that has affected life of every individual in the world. It is caused by a novel Corona virus strain that has caused seventh Corona virus infection that has affected human population, named as “COVID-19” virus by the World Health Organization. Previously, six Corona virus infections have affected humans but those caused by SARS-CoV and MERS-CoV have proved to be more lethal. Angiotensin Converting Enzyme 2 (ACE2) has been found as the receptor for COVID-19 through which cellular entry of the virus is mediated into the body. These receptors are abundantly present in the oral cavity especially on the epithelial cells of the tongue, oral mucosa and the gingiva. Saliva is an oral bio-fluid of the oral cavity in which high titres of the virus have been identified during early and later stages of infection. Saliva collection is a non-invasion method and can act as a diagnostic tool for COVID-19 disease. Common oral symptoms of the disease include transient loss of taste, smell and dryness of mouth. Precautionary measures must be taken by dentist before carrying out any dental procedure for safety of the health care professional, staff and also the patient. Dental community must think of the “new normal” regarding clinical dental care in light of post-COVID-19 situation.